The conflict over water between Palestine and the Zionist entity - خزامة, عاطف (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research talks about the issue of the Palestinian-Zionist conflict on the issue of water, and deals with the Zionist plans that the Zionist movement has worked with since its inception in order to plunder the sources of water wealth in Palestine, as well as the actual implementation of those plans, speaking of the most important stages through which the Zionist entity controlled the most important The water sources in Palestine since the beginning of the British Mandate over Palestine, through the catastrophe of 1948 AD, the setback of 1967 AD, and the accompanying unjust Zionist measures aimed at plundering Arab and Palestinian water, in order to provide the most important vital ingredients for the continued presence of the Zionist entity on the Palestinian lands